Positive electrode for rechargeable lithium battery and rechargeable lithium battery including same
By introducing a thermal suppression layer into the positive electrode of the rechargeable lithium battery, the safety problem of lithium battery during physical impact or puncture is solved, and the prevention of explosion and fire is achieved, which improves the safety of the battery.
Patent Information
- Application Number
- CN202410538643.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-14
- Filing Date
- 2024-04-30
- Publication Date
- 2025-01-14
AI Technical Summary
Existing rechargeable lithium batteries are prone to explosion and fire when subjected to physical impact or piercing sharp objects, and lack effective safety guarantees.
A positive electrode is designed, including a current collector, a positive electrode active material layer and a thermal suppression layer. The thermal suppression layer is located between the current collector and the positive electrode active material layer, and the thickness ratio is about 1:5 to 1:20 to suppress heating and Improve safety.
Through the design of the thermal suppression layer, the safety of lithium batteries during physical impact or puncture is significantly improved, the occurrence of explosion and fire is avoided, and the stability and safety of the batteries are ensured.
Smart Images

Figure CN119314988A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure described herein relate to a positive electrode for a rechargeable lithium battery and a rechargeable lithium battery including the positive electrode. Background Art
[0002] Recently, the rapid development of electronic devices using batteries, such as mobile phones, laptop computers, and / or electric vehicles, has increased the demand for rechargeable lithium batteries having relatively high capacity and light weight.
[0003] Such a rechargeable lithium battery may include a positive electrode including a positive active material, a negative electrode including a negative active material, a separator between the positive electrode and the negative electrode, and an electrolyte. Summary of the invention
[0004] Aspects according to one or more embodiments relate to a positive electrode for a rechargeable lithium battery exhibiting improved safety.
[0005] An aspect according to one or more embodiments is directed to a rechargeable lithium battery including the positive electrode.
[0006] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented disclosed embodiments.
[0007] One or more embodiments provide a positive electrode, comprising: a current collector; a positive electrode active material layer comprising a positive electrode active material; and a heat inhibition layer located between the current collector and the positive electrode active material layer, wherein a thickness ratio of the heat inhibition layer to the positive electrode active material layer is about 1:5 to about 1:20.
[0008] An embodiment provides a rechargeable lithium battery including: a positive electrode; a negative electrode including a negative active material; and an electrolyte.
[0009] Other embodiments are included in the detailed description which follows.
[0010] A positive electrode for a rechargeable lithium battery may exhibit excellent or suitable safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a schematic diagram showing a positive electrode for a rechargeable lithium battery.
[0012] Figure 2 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. DETAILED DESCRIPTION
[0013] Hereinafter, embodiments of the present disclosure are described in more detail. However, these embodiments are merely examples, the present disclosure is not limited thereto, and the present disclosure is defined by the scope of the claims.
[0014] The terms used in the specification are used to explain the embodiments but are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0015] The term "combination thereof" may include mixtures, laminates, composites, copolymers, alloys, blends or reactants of the components.
[0016] The terms "comprising", "including" or "having" are intended to indicate the presence of executed characteristics, quantities, steps, constituent elements or combinations thereof, but it should be understood that the possibility of the presence or addition of one or more other characteristics, quantities, steps, constituent elements or combinations thereof is not precluded.
[0017] In addition, the terms "about (approximately)" and "substantially" used throughout this specification refer to the mentioned meanings with inherent preparation and material tolerance errors when present, and are used in the sense of being close to or approaching the value. They are used to help understand the present disclosure and prevent or reduce the unfair use of the present disclosure by irresponsible infringers in the case of referring to exact values or absolute values. For example, "about (approximately)" can mean within one or more standard deviations, or within ±30%, ±20%, ±10% or ±5% of the stated value.
[0018] Here, “or” should not be interpreted as an exclusive meaning, for example, “A or B” is interpreted as including A, B and / or A+B, etc.
[0019] As used herein, when no definition is provided in addition, particle diameter or size can be an average particle diameter. This particle diameter represents an average particle diameter or average particle size (D50) in which the cumulative volume is about 50% by volume in the particle size distribution. The average particle size (D50) can be measured by a method suitable for those skilled in the art (e.g., by a particle size analyzer or by a transmission electron microscope image or a scanning electron microscope image). In some embodiments, data analysis is performed using a dynamic light scattering measurement device, and the number of particles in each size range is counted, so that the average particle diameter (D50) value can be easily obtained by calculation. In another embodiment, it can be measured by a laser diffraction method. Laser diffraction can be obtained by distributing the particles to be measured in a distribution solvent and introducing it into a commercially available laser diffraction particle measurement device (e.g., MT 3000 available from Microtrac, Ltd.), irradiating an ultrasonic wave of about 28kHz with a power of 60W, and calculating the average particle diameter (D50) in the particle distribution of 50% standard in the measuring device. In the present disclosure, when the particle is spherical, the “diameter” means the particle diameter or the average particle diameter, and when the particle is non-spherical, the “diameter” means the major axis length or the average major axis length.
[0020] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. As used herein, when expressions such as "at least one of...", "one of...", and "selected from..." are followed / preceded by a list of elements, the entire list of elements is modified, rather than the individual elements of the list. For example, "at least one of a, b, and c", "at least one of a, b, and c", etc. can mean only a, only b, only c, (e.g., simultaneously) both a and b, (e.g., simultaneously) both a and c, (e.g., simultaneously) both b and c, all of a, b, and c, or variations thereof.
[0021] In addition, any numerical range listed here is intended to include all sub-ranges of the same numerical precision contained in the listed range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the listed minimum value 1.0 and the listed maximum value 10.0 (including the listed minimum value 1.0 and the listed maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit listed here is intended to include all lower numerical limits contained therein, and any minimum numerical limit listed in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification (including claims) to explicitly list any sub-ranges contained in the range explicitly listed here.
[0022] One or more embodiments provide a positive electrode for a rechargeable lithium battery, the positive electrode comprising: a current collector; a positive active material layer including a positive active material; and a layer for suppressing heat generation (ie, a heat suppression layer) between the current collector and the positive active material layer. Figure 1 The positive electrode 1 is schematically shown, and includes a current collector 3 and a positive electrode active material layer 5 , and a heat suppression layer 7 between the current collector 3 and the positive electrode active material layer 5 . Figure 1 The boundary between the positive electrode active material layer 5 and the heat inhibition layer 7 is shown to be clearly separated, but the positive electrode according to one or more embodiments is not limited thereto. For example, the boundary at which the positive electrode active material layer contacts the heat inhibition layer may not be clearly separated, and they may overlap (or mix) with each other. At the boundary at which the positive electrode active material layer contacts the heat inhibition layer, there may be an area where the components constituting the positive electrode active material layer and the heat inhibition layer coexist. Such an area may be generated during preparation. The components constituting the positive electrode active material layer may be partially impregnated into the surface of the heat inhibition layer.
[0023] The thickness ratio of the heat inhibition layer to the positive electrode active material layer may be about 1: 5 to about 1: 20 or about 1: 8 to about 1: 15. If the thickness ratio of the heat inhibition layer to the positive electrode active material layer is within this range (e.g., when the thickness ratio of the heat inhibition layer to the positive electrode active material layer is within this range), the effect of improving safety due to the use of the heat inhibition layer can be effectively obtained.
[0024] In one or more embodiments, if the battery is pierced by a sharp object (such as a nail) or subjected to physical impact (such as penetration) (for example, when the battery is pierced by a sharp object (such as a nail) or subjected to physical impact (such as penetration)), the heat inhibition layer is used to enhance safety by preventing or reducing the occurrence of battery explosion and fire, etc. If included in the thickness ratio (for example, when included in the thickness ratio), such enhancement of safety is achieved. If the thickness ratio of the heat inhibition layer and the positive electrode active material layer is outside the range (for example, when the thickness ratio of the heat inhibition layer and the positive electrode active material layer is outside the range), for example, greater than about 1 / 5 (which indicates that the thickness of the heat inhibition layer is too thick), the capacity is relatively reduced. If it is less than about 1 / 20 (which indicates that the thickness of the heat inhibition layer is too thin) (for example, when it is less than about 1 / 20 (which indicates that the thickness of the heat inhibition layer is too thin)), it may not be possible to fully obtain the improvement in safety.
[0025] In one or more embodiments, the heat inhibition layer may have a thickness of about 1 μm to about 10 μm, about 1 μm to about 8 μm, or about 1 μm to about 6 μm.
[0026] The thickness of the positive active material layer may be about 30 μm to about 200 μm, about 50 μm to about 150 μm, or about 80 μm to about 120 μm.
[0027] It is appropriate or suitable that the thickness of the heat inhibition layer and the positive electrode active material layer are included in the range, and the thickness ratio of the heat inhibition layer and the positive electrode active material layer is within the range. Even if the thickness of the heat inhibition layer and the positive electrode active material layer both fall within the range (for example, when the thickness of the heat inhibition layer and the positive electrode active material layer both fall within the range), if the thickness ratio of the heat inhibition layer and the positive electrode active material layer is outside the range (for example, when the thickness ratio of the heat inhibition layer and the positive electrode active material layer is outside the range), the desired or suitable effect may not be achieved. For example, the thickness of the heat inhibition layer is 2 μm and the thickness of the positive electrode active material layer is 200 μm, which corresponds to a thickness ratio of the heat inhibition layer and the positive electrode active material layer of 1:100, which is inappropriate or inappropriate.
[0028] If the thickness of the heat suppression layer is within this range (eg, when the thickness of the heat suppression layer is within this range), appropriate safety effects and capacity may be appropriately obtained.
[0029] Layer for suppressing heat generation
[0030] In one or more embodiments, the heat suppression layer may include a compound for suppressing heat generation, the compound being selected from FeF3, FeF2, CuF2, MoCl5, NiF2, FeCl3, CoF3, CoF2, MnF3, NbF3, TiF4, ZnF2, BiF3, TiO2, SeO2, CuO, CuO2, P2S5, P4S7, NiS2, CoS2, Co3O4, FeS2, MoO3, SiS2, MnO2, Fe2O3, V2O5, LiFeF3, LiFeF2, LiCuF2, LiNiF2, LiFeCl3, LiCoF3, LiCoF2, LiMnF3, LiNbF3, LiTiF4, LiBiF3, LiTiO2, Li4Ti5O 12, LiSeO2, LiCuO, Li2CuO2, Li2P2S5, LiNiS2, LiCoS2, LiCo3O4, LiFeS2, LiMoO3, Li2SiS2, LiMnO2, LiFe2O3, LiV2O5, Li2S8 and combinations thereof (for example, the compound is FeF3, FeF2, CuF2, MoCl5, NiF2, FeCl3, CoF3, CoF2, MnF3, NbF3, TiF4, Z nF2, BiF3, TiO2, SeO2, CuO, CuO2, P2S5, P4S7, NiS2, CoS2, Co3O4, FeS2, MoO3, SiS2, MnO2, Fe2O3, V2O5, LiF eF3, LiFeF2, LiCuF2, LiNiF2, LiFeCl3, LiCoF3, LiCoF2, LiMnF3, LiNbF3, LiTiF4, LiBiF3, LiTiO2, Li4Ti5O 12 , LiSeO2, LiCuO, Li2CuO2, Li2P2S5, LiNiS2, LiCoS2, LiCo3O4, LiFeS2, LiMoO3, Li2SiS2, LiMnO2, LiFe2O3, LiV2O5, Li2S8, and combinations thereof). In another embodiment, the compound for suppressing heat generation may include (for example, be) FeF3, TiO2, LiFeF3, LiFeF2, or a combination thereof. In another embodiment, the compound for suppressing heat generation may include (for example, be) FeF3, TiO2, or a combination thereof.
[0031] Such a compound for suppressing heat generation may have a nanometer size, for example, may have an average particle size D50 of about 1 μm or less. The compound for suppressing heat generation may have an average particle size D50 of about 100 nm to about 900 nm or about 300 nm to about 700 nm. If the compound for suppressing heat generation has a nanometer size (for example, when the compound for suppressing heat generation has a nanometer size), for example, having an average particle size within this range, the heat suppression layer can be formed more tightly.
[0032] The heat suppression layer according to one or more embodiments may have a smooth surface. This is due to the pressurization during the preparation of the positive electrode. Such a smooth heat suppression layer may make it easy to impregnate with a liquid electrolyte.
[0033] The heat suppression layer may further include a binder. The binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, or a combination thereof.
[0034] In the heat suppression layer according to one or more embodiments, the mixing ratio of the compound for suppressing heat generation and the binder may be a weight ratio of about 200: 1 to about 20: 1, about 150: 1 to about 50: 1, or about 120: 1 to about 80: 1. If the mixing ratio of the compound for suppressing heat generation and the binder is satisfied within this range (e.g., when the mixing ratio of the compound for suppressing heat generation and the binder is satisfied within this range), the effect of controlling thermal runaway of the battery can be obtained to a large extent.
[0035] Positive electrode active material layer
[0036] The positive active material included in the positive active material layer may be any positive active material used for a rechargeable lithium battery.
[0037] The positive electrode active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. In other embodiments, one or more composite oxides of metals selected from cobalt, manganese, nickel, and combinations thereof and lithium may be used. For example, a compound represented by one of the following chemical formulas may be used. Li a A 1-b X b D 1 2(0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a E 1-b X b O 2-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a E 2-b X b O 4-c1 D 1 c1 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c1≤0.05); Li a Ni1-b-c Co b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b- c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1)Lia CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4(0.90≤a≤1.8)
[0038] In the above chemical formula, A is selected from Ni, Co, Mn or a combination thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D 1 is selected from O, F, S, P or a combination thereof; E is selected from Co, Mn or a combination thereof; T is selected from F, S, P or a combination thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is selected from Ti, Mo, Mn or a combination thereof; Z is selected from Cr, V, Fe, Sc, Y or a combination thereof; J is selected from V, Cr, Mn, Co, Ni, Cu or a combination thereof; and L 1 Selected from Mn, Al or a combination thereof.
[0039] In addition, the compound may have a coating on the surface, or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from the group consisting of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxygen-containing carbonate of a coating element, and a hydroxycarbonate of a coating element. The compound for the coating may be amorphous or crystalline. The coating element included in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be provided by using these elements in a compound in a method that has no adverse effect on the properties of the positive active material, for example, the method may include any coating method (such as spraying and / or dipping, etc.), but because it is applicable in the relevant field, it is not described in more detail.
[0040] In the positive electrode, the amount of the positive active material may be about 90 wt % to about 99.5 wt % based on the total weight of the positive active material layer.
[0041] The positive electrode active material layer includes a binder and a conductive material. Here, the binder and the conductive material may be included in an amount of about 0.25 wt % to about 5 wt % based on the total amount of the positive electrode active material layer.
[0042] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of the binder may be polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin and / or nylon, but are not limited thereto.
[0043] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change, and examples thereof may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black and / or carbon fiber, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver, etc.; conductive polymers such as polyphenylene derivatives; and / or one or more mixtures thereof (and / or combinations thereof).
[0044] The current collector may include Al, but is not limited thereto.
[0045] Positive electrode preparation
[0046] The positive electrode according to one or more embodiments may be manufactured by forming a heat inhibition layer on a current collector and preparing a positive active material layer on the heat inhibition layer.
[0047] The heat inhibition layer may be formed by coating a heat inhibition layer composition including a heat inhibition compound, a binder and a first solvent on a current collector and drying the first solvent. The first solvent may be N-methylpyrrolidone or the like, but is not limited thereto.
[0048] The amount of the compound for suppressing heat generation and the binder may be used so that the mixing ratio of the compound for suppressing heat generation and the binder in the prepared layer for suppressing heat generation is about 9:1 to 39:1, about 15:1 to about 30:1, or about 20:1 to about 25:1 by weight.
[0049] The positive active material layer may be prepared by coating a positive active material composition including a positive active material, a binder, a conductive material, and a second solvent on the heat inhibition layer and drying the positive active material layer. After drying the positive active material layer, pressurization may be performed.
[0050] The second solvent may be N-methylpyrrolidone or the like, but is not limited thereto.
[0051] Rechargeable lithium battery
[0052] Other embodiments provide a rechargeable lithium battery including a positive electrode, a negative electrode including a negative active material, and an electrolyte.
[0053] The negative electrode includes a current collector and a negative active material layer, and the negative active material layer includes a negative active material.
[0054] The negative electrode active material includes a material that can reversibly intercalate / deintercalate lithium ions, lithium metal, a lithium metal alloy, a material that can be doped / dedoped with lithium, or a transition metal oxide.
[0055] The material that reversibly embeds / deintercalates lithium ions may be a carbon material, which may be any commonly used carbon-based negative electrode active material for lithium secondary batteries. Examples of materials that reversibly embed / deintercalate lithium ions may be crystalline carbon, amorphous carbon, or a combination thereof. Crystalline carbon may be non-shaped (unspecified shape), or may be natural graphite or artificial graphite in the form of flakes, plates, spheres, or fibers, and amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, and / or calcined coke, etc.
[0056] The lithium metal alloy can be an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and / or Sn.
[0057] The material capable of doping / dedoping lithium may be a Si-based active material, a Sn-based active material, or a combination thereof. The Si-based active material may be Si, a Si-C composite, SiO x(0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and not Si), or a combination thereof. The Sn-based active material can be Sn, SnO2, an Sn-R alloy (where R is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and not Sn), or a combination thereof. At least one of the Si-based active material and the Sn-based active material can be mixed with SiO2. The elements Q and R can (both) be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or combinations thereof.
[0058] In one or more embodiments, the Si-C composite can include silicon particles and an amorphous carbon coating formed on the surface of the silicon particles. For example, the Si-C composite can include silicon nanoparticles and an amorphous carbon coating located on the surface of the silicon nanoparticles. The Si-C composite can include secondary particles in which primary silicon particles (primary Si particles) are agglomerated and an amorphous carbon coating located on the surface of the secondary particles. Amorphous carbon can also be located between the primary silicon particles, and / or for example, the primary silicon particles or silicon can be coated with amorphous carbon. In one or more embodiments, the Si-C (silicon-carbon) composite can include a core in which silicon particles are distributed in an amorphous carbon matrix and an amorphous carbon coating coated on the surface of the core.
[0059] Since the secondary particles are located at the center of the Si-C composite, the secondary particles can be referred to as the core or the central part. The amorphous carbon coating can be referred to as the outer part or the shell.
[0060] The primary silicon particles can be nanosilicon particles. The particle size of the nanosilicon particles can be from about 10 nm to about 1,000 nm, and according to another embodiment, can be from about 20 nm to about 900 nm, from about 20 nm to about 800 nm, from about 20 nm to about 500 nm, from about 20 nm to about 300 nm, or from about 20 nm to about 150 nm. If the particle size of silicon is within this range (e.g., when the particle size of silicon is within this range), excessive volume expansion caused during charging and discharging can be suppressed or reduced, and damage to the conduction path due to particle fragmentation can be prevented or reduced.
[0061] The particle size of the silicon secondary particles is not limited thereto.
[0062] If the Si-C composite includes silicon particles and an amorphous carbon coating (for example, when the Si-C composite includes silicon particles and an amorphous carbon coating), the amount of the silicon particles may be about 30 wt % to about 70 wt % or about 40 wt % to about 65 wt % based on the total 100 wt % of the silicon-carbon composite. The amount of the amorphous carbon coating may be about 30 wt % to about 70 wt % or about 35 wt % to about 60 wt % based on the total 100 wt % of the silicon-carbon composite.
[0063] The Si-C composite may further include crystalline carbon. If the Si-C composite further includes crystalline carbon (for example, when the Si-C composite further includes crystalline carbon), it may include an agglomeration product in which silicon particles and crystalline carbon are agglomerated and an amorphous carbon coating on the surface of the agglomeration product.
[0064] In one or more embodiments, the secondary particles or cores may also include crystalline carbon. If the Si-C composite also includes crystalline carbon (e.g., when the Si-C composite also includes crystalline carbon), the Si-C composite may include secondary particles in which silicon primary particles and crystalline carbon are agglomerated and an amorphous carbon coating located on the surface of the secondary particles. The crystalline carbon may be natural graphite or artificial graphite of unspecified shape, flaky, plate-like, spherical or fibrous shape.
[0065] If the Si-C composite further includes crystalline carbon (for example, when the Si-C composite further includes crystalline carbon), the amount of the silicon nanoparticles may be about 20 wt % to about 70 wt % or about 25 wt % to about 65 wt % based on the total 100 wt % of the Si-C composite. The amount of amorphous carbon may be about 25 wt % to about 70 wt % or about 25 wt % to about 60 wt % based on the total 100 wt % of the Si-C composite, and the amount of crystalline carbon may be about 1 wt % to about 20 wt % or about 5 wt % to about 15 wt %.
[0066] The particle size of the Si—C composite can be appropriately adjusted and does not need to be limited.
[0067] The thickness of the amorphous carbon coating layer may be appropriately adjusted, and may be, for example, about 5 nm to about 100 nm.
[0068] In one or more embodiments, a Si-based active material is included as the first negative electrode active material, and crystalline carbon may be included as the second negative electrode active material. The mixing ratio of the first negative electrode active material and the second negative electrode active material may be a weight ratio of about 1:99 to about 99:1. For example, the negative electrode active material may include the first negative electrode active material and the second negative electrode active material in a weight ratio of about 1:99 to about 50:50 or a weight ratio of about 5:95 to about 20:80.
[0069] The negative electrode active material layer may include a binder and also include a conductive material. In the negative electrode active material layer, the amount of the binder may be about 1wt% to about 5wt% based on the total amount of the negative electrode active material layer. In addition, when the negative electrode active material layer includes a conductive material, the negative electrode active material layer includes about 90wt% to about 98wt% of the negative electrode active material, about 1wt% to about 5wt% of the binder, and about 1wt% to about 5wt% of the conductive material.
[0070] The binder improves the binding properties between the negative electrode active material particles and between the negative electrode active material particles and the current collector. The binder includes a non-aqueous binder, an aqueous binder, or a combination thereof.
[0071] The non-aqueous binder may be ethylene propylene copolymer, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0072] The aqueous binder may include styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0073] The binder of the negative electrode may include a cellulose compound. In other embodiments, the binder of the negative electrode may include an aqueous binder mixed with a cellulose compound. The cellulose compound includes one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and their alkali metal salts. The alkali metal may be Na, K or Li. The cellulose compound is referred to as a thickener because it can impart viscosity, or it can be used as a binder, and therefore, it can be referred to as a binder. The amount of the cellulose compound can be appropriately adjusted within the amount of the binder, and is not limited thereto, and for example, based on 100 parts by weight of the negative electrode active material, the amount of the cellulose compound can be from about 0.1 parts by weight to about 3 parts by weight.
[0074] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may be: a carbon-based material such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and / or carbon fiber, etc.; a metal-based material including metal powder or metal fiber of copper, nickel, aluminum, and / or silver, etc.; a conductive polymer such as a polyphenylene derivative; or a mixture thereof.
[0075] The current collector may include one selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof, but is not limited thereto.
[0076] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0077] The non-aqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.
[0078] The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, or an aprotic solvent.
[0079] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) and / or butylene carbonate (BC) etc. Esters solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone and / or caprolactone etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran and / or tetrahydrofuran etc. In addition, ketone solvents may include cyclohexanone etc. In some embodiments, the alcohol solvent may include ethanol and / or isopropanol, etc., and the aprotic solvent may include nitrile (such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon, and may include a double bond, an aromatic ring or an ether bond)), amide (such as dimethylformamide, etc.), dioxolane (such as 1,3-dioxolane and / or 1,4-dioxolane, etc.) and / or sulfolane, etc.
[0080] The non-aqueous organic solvent can be used alone or in a mixture. If the non-aqueous organic solvent is used in a mixture (e.g., when the non-aqueous organic solvent is used in a mixture), the mixing ratio can be controlled or selected according to the desired battery performance, and this can be very suitable for technicians in the relevant field.
[0081] If a non-aqueous organic solvent is mixed and used (for example, when a non-aqueous organic solvent is mixed and used), a mixed solvent of a cyclic carbonate and a chain carbonate, a mixed solvent of a cyclic carbonate and a propionate solvent, or a mixed solvent of a cyclic carbonate, a chain carbonate and a propionate solvent can be used. The propionate solvent can be methyl propionate, ethyl propionate, propyl propionate or a combination thereof.
[0082] If cyclic carbonate is mixed with linear carbonate or cyclic carbonate is mixed with propionate solvent (for example, when cyclic carbonate is mixed with linear carbonate or cyclic carbonate is mixed with propionate solvent), they can be mixed with a volume ratio of about 1:1 to about 1:9, so the performance of the electrolyte solution can be improved. If cyclic carbonate, linear carbonate and propionate solvent are mixed (for example, when cyclic carbonate, linear carbonate and propionate solvent are mixed), they can be mixed with a volume ratio of about 1:1:1 to about 3:3:4. The mixing ratio of the solvent can be appropriately adjusted according to the desired property.
[0083] The non-aqueous organic solvent may further include an aromatic hydrocarbon solvent and a carbonate solvent. The carbonate solvent and the aromatic hydrocarbon solvent may be mixed together in a volume ratio of about 1:1 to about 30:1.
[0084] The aromatic hydrocarbon solvent may be an aromatic hydrocarbon compound represented by Chemical Formula 1.
[0085] Chemical formula 1
[0086]
[0087] In Chemical Formula 1, R1 to R6 may all be independently the same or different, and are selected from hydrogen, halogen, C1 to C10 alkyl, halogenated alkyl, and combinations thereof.
[0088] Examples of aromatic hydrocarbon solvents may be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, 2,3-fluorotoluene, and 1,2-dichlorobenzene. -difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and one or more combinations thereof.
[0089] The electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound represented by Chemical Formula 2 as an additive for improving cycle life.
[0090] Chemical formula 2
[0091]
[0092] In Chemical Formula 2, R7 and R8 may be independently the same or different, and may be independently hydrogen, halogen, cyano (CN), nitro (NO2) or fluorinated C1 to C5 alkyl, provided that at least one of R7 and R8 is halogen, cyano (CN), nitro (NO2) or fluorinated C1 to C5 alkyl, and R7 and R8 are not hydrogen at the same time (e.g., not concurrently).
[0093] Examples of ethylene carbonate compounds may include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate and / or fluoroethylene carbonate. In the case of further using additives to improve cycle life, the amount of the additive may be appropriately controlled or selected within an appropriate or suitable range.
[0094] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions to the battery, basically operates the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4 and / or LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein, x and y are natural numbers, for example, integers from about 1 to about 20), at least one or two supporting salts among LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalate)borate: LiBOB) and lithium difluoro(oxalate)borate (LiDFOB). The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the lithium salt is included in the above concentration range (for example, when the lithium salt is included in the above concentration range), the electrolyte may have excellent or suitable performance and lithium ion mobility due to optimal or suitable electrolyte conductivity and viscosity.
[0095] According to the type or kind of the rechargeable lithium battery, the separator may be provided between the positive electrode and the negative electrode. The separator may use polyethylene, polypropylene, polyvinylidene fluoride or a multilayer having two or more layers thereof, and may be a mixed multilayer (such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator and / or a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0096] The separator may include a porous substrate and a ceramic-containing coating on at least one surface of the porous substrate. The ceramic may include SiO2, Al2O3, Al(OH)3, AlO(OH), TiO2, BaTiO2, ZnO2, Mg(OH)2, MgO, Ti(OH)4, ZrO2, aluminum nitride, silicon carbide, boron nitride, or a combination thereof.
[0097] According to some embodiments, the diaphragm may also be a composite porous diaphragm, which includes a porous substrate and a functional layer located on the porous substrate. The functional layer may have additional functions, for example, it may be at least one of a heat-resistant layer and an adhesive layer. The heat-resistant layer may include a heat-resistant resin and an optional filler. In other embodiments, the adhesive layer may include an adhesive resin and an optional filler. The filler may be an organic filler, an inorganic filler, or a combination thereof. The heat-resistant resin and the adhesive resin may be any material that can be used in the diaphragm in the related art.
[0098] Figure 2 is a perspective view of a rechargeable lithium battery according to some embodiments of the present disclosure. The rechargeable lithium battery according to one or more embodiments is shown as a prismatic battery, but is not limited thereto and may include batteries of various shapes such as cylindrical batteries and pouch batteries.
[0099] Reference Figure 2 The rechargeable lithium battery 100 according to the embodiment may include an electrode assembly 40 manufactured by winding a separator 30 disposed between a positive electrode 10 and a negative electrode 20 and a case 50 accommodating the electrode assembly 40. An electrolyte may be impregnated in the positive electrode 10, the negative electrode 20, and the separator 30.
[0100] Hereinafter, examples and comparative examples of the present disclosure are described. However, these examples shall not be interpreted as limiting the scope of the present disclosure in any sense.
[0101] Example 1
[0102] 95 wt % of FeF 3 having an average particle size (D50) of 513 nm and 5 wt % of a polyethylene binder were mixed in an N-methylpyrrolidone solvent as a slurry for a heat suppression layer.
[0103] 98.35 wt % of LiCoO 2 positive electrode active material, 0.8 wt % of polyvinylidene fluoride binder and 0.85 wt % of Ketjen black conductive material were mixed in N-methylpyrrolidone solvent to prepare positive electrode active material layer slurry.
[0104] The slurry for the heat inhibition layer was coated on the Al foil current collector and dried to prepare the heat inhibition layer, and then the positive electrode active material layer slurry was coated on the heat inhibition layer, dried, and then pressed to prepare the positive electrode. In the prepared positive electrode, the thickness of the heat inhibition layer was 8.3 μm, and the thickness of the positive electrode active material layer was 41.7 μm. Therefore, the thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:5.
[0105] A 4500mAh pouch cell was fabricated using the positive electrode, artificial graphite negative electrode and electrolyte. 1.35M LiPF6 dissolved in a mixture of ethylene carbonate, propylene carbonate, ethyl propionate and propyl propionate (volume ratio 10:15:30:45) was used as the electrolyte.
[0106] Example 2
[0107] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 4.5 μm and a positive electrode active material layer having a thickness of 45 μm were prepared using the slurry for the heat inhibition layer of Example 1 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:10.
[0108] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0109] Example 3
[0110] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 2.4 μm and a positive electrode active material layer having a thickness of 47.6 μm were prepared using the slurry for the heat inhibition layer of Example 1 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:20.
[0111] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0112] Example 4
[0113] A positive electrode was prepared by the same procedure as in Example 1 except that LiFeF3 having an average particle size (D50) of 531 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:5.
[0114] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0115] Example 5
[0116] A positive electrode was prepared by the same procedure as in Example 2 except that LiFeF3 having an average particle size (D50) of 531 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:10.
[0117] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0118] Example 6
[0119] A positive electrode was prepared by the same procedure as in Example 3 except that LiFeF3 having an average particle size (D50) of 531 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:20.
[0120] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0121] Example 7
[0122] A positive electrode was prepared by the same procedure as in Example 1 except that LiFeF2 having an average particle size (D50) of 524 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:5.
[0123] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0124] Example 8
[0125] A positive electrode was prepared by the same procedure as in Example 2 except that LiFeF2 having an average particle size (D50) of 524 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:10.
[0126] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0127] Example 9
[0128] A positive electrode was prepared by the same procedure as in Example 3 except that LiFeF2 having an average particle size (D50) of 524 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:20.
[0129] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0130] Example 10
[0131] A positive electrode was prepared by the same procedure as in Example 1 except that TiO2 having an average particle size (D50) of 671 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:5.
[0132] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0133] Example 11
[0134] A positive electrode was prepared by the same procedure as in Example 2 except that TiO2 having an average particle size (D50) of 671 nm was used as the heat inhibiting compound. The thickness ratio of the heat inhibiting layer to the positive electrode active material layer was 1:10.
[0135] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0136] Example 12
[0137] A positive electrode was prepared by the same procedure as in Example 3 except that TiO2 having an average particle size (D50) of 671 nm was used as a compound for suppressing heat generation. The thickness ratio of the heat suppression layer to the positive electrode active material layer was 1:20.
[0138] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0139] Example 13 to Example 63
[0140] A slurry for a heat generation suppressing layer was prepared by the same procedure as in Example 1 except that the compound shown in Table 1 was used instead of FeF 3 as the heat suppressing compound.
[0141] A positive electrode was prepared by the same procedure as in Example 2, except that a heat suppression layer having a thickness of 4.5 μm and a positive active material layer having a thickness of 45 μm were prepared using the slurry for the heat suppression layer and the positive active material layer slurry of Example 1. The thickness ratio of the heat suppression layer to the positive active material layer was 1:10.
[0142] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0143] Comparative Example 1
[0144] 98.35 wt % of LiCoO 2 positive active material, 0.5 wt % of polyvinylidene fluoride binder, and 0.85 wt % of Ketjen black conductive material were mixed in N-methylpyrrolidone solvent to prepare positive active material layer slurry.
[0145] The positive electrode active material layer slurry was coated on an Al foil current collector, dried and pressed to prepare a positive electrode. In the prepared positive electrode, the thickness of the positive electrode active material layer was 50 μm.
[0146] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0147] Comparative Example 2
[0148] A positive electrode was prepared by the same steps as in Example 1, except that a heat suppression layer having a thickness of 10 μm and a positive active material layer having a thickness of 40 μm were prepared using the slurry for the heat suppression layer of Example 1 and the positive active material layer slurry of Example 1. The thickness ratio of the heat suppression layer to the positive active material layer was 1:4.
[0149] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0150] Comparison Example 3
[0151] A positive electrode was prepared by the same steps as in Example 1, except that a heat suppression layer having a thickness of 2.3 μm and a positive active material layer having a thickness of 47.7 μm were prepared using the slurry for the heat suppression layer of Example 1 and the positive active material layer slurry of Example 1. The thickness ratio of the heat suppression layer to the positive active material layer was 1:21.
[0152] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0153] Comparison Example 4
[0154] A positive electrode was prepared by the same steps as in Example 1, except that a heat suppression layer having a thickness of 10 μm and a positive active material layer having a thickness of 40 μm were prepared using the slurry for the heat suppression layer of Example 4 and the positive active material layer slurry of Example 1. The thickness ratio of the heat suppression layer to the positive active material layer was 1:4.
[0155] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0156] Comparative Example 5
[0157] A positive electrode was prepared by the same steps as in Example 1, except that a heat suppression layer having a thickness of 2.3 μm and a positive active material layer having a thickness of 47.7 μm were prepared using the slurry for the heat suppression layer of Example 4 and the positive active material layer slurry of Example 1. The thickness ratio of the heat suppression layer to the positive active material layer was 1:21.
[0158] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0159] Comparative Example 6
[0160] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 10 μm and a positive electrode active material layer having a thickness of 40 μm were prepared using the slurry for the heat inhibition layer of Example 7 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:4.
[0161] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0162] Comparative Example 7
[0163] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 2.3 μm and a positive electrode active material layer having a thickness of 47.7 μm were prepared using the slurry for the heat inhibition layer of Example 7 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:21.
[0164] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0165] Comparative Example 8
[0166] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 10 μm and a positive electrode active material layer having a thickness of 40 μm were prepared using the slurry for the heat inhibition layer of Example 10 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:4.
[0167] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0168] Comparative Example 9
[0169] A positive electrode was prepared by the same steps as in Example 1, except that a heat inhibition layer having a thickness of 2.3 μm and a positive electrode active material layer having a thickness of 47.7 μm were prepared using the slurry for the heat inhibition layer of Example 10 and the positive electrode active material layer slurry of Example 1. The thickness ratio of the heat inhibition layer to the positive electrode active material layer was 1:21.
[0170] A 4500 mAh pouch-type battery cell was manufactured through the same steps as those in Example 1 using the positive electrode as well as the negative electrode and electrolyte of Example 1.
[0171] Experimental Example 1: Test for penetration evaluation
[0172] The 4500mAh pouch-type battery cells according to Examples 1 to 63 and Comparative Examples 1 to 9 were fully charged to 4.47V cutoff at SOC100 (charged to 100% of the charge capacity based on the total charge capacity of the battery cell if the battery cell is charged (e.g., when the battery cell is charged).
[0173] A fully charged battery cell was pierced completely through the center using a 5 mm diameter needle at a speed of 50 mm / sec.
[0174] Among these results, the results of Examples 1 to 63 are shown in Table 1, and the results of Comparative Examples 1 to 9 are shown in Table 2.
[0175] In Tables 1 and 2, O indicates ignition, and X indicates no ignition.
[0176] Experimental Example 2: Measurement of AC-IR (resistance) and first cycle formation charge
[0177] Regarding the pouch-type battery cells of Examples 1 to 63 and Comparative Examples 1 to 9, AC-IR was measured by using a 1kHz AC resistance measuring device. Among the measured AC-IR results, the results of Examples 1 to 63 are shown in Table 1, and the results of Comparative Examples 1 to 9 are shown in Table 2.
[0178] The battery cell for which AC-IR was measured was subjected to formation charging at 0.1C (450 mAh) to check whether charging occurred.
[0179] Table 1
[0180]
[0181]
[0182]
[0183]
[0184] Table 2
[0185]
[0186] As shown in Table 1, Examples 1 to 63, which include a heat suppression layer between the current collector and the positive electrode active material layer and have a thickness ratio of 1:5 to 1:20, exhibit an AC resistance of less than 1000 mΩ, thereby enabling formation charge and discharge. Therefore, a full charge penetration test can be performed, and as a result, no fire occurs. From these results, it can be seen that the battery cells of Examples 1 to 63 exhibit excellent safety.
[0187] As shown in Table 2, Comparative Example 1 without a heat suppression layer had a low AC resistance of 41.8 mΩ, enabling formation charge and discharge. Therefore, a full charge penetration test was enabled, but ignition occurred, indicating deteriorated safety.
[0188] Comparative Examples 2, 4, 6, and 8 including those having a very thick heat suppression layer exhibited surprisingly high AC resistance of 1000 mΩ or more. Therefore, formation charge and discharge could not be performed, and thus a full charge penetration test could not be conducted.
[0189] In the case of Comparative Examples 3, 5, 7, and 9 where the heat suppression layer was too thin, AC resistance was low (less than 1000 mΩ), allowing formation charge and discharge to be performed. However, the occurrence of ignition indicated poor safety.
[0190] The electronic device, vehicle and / or battery (e.g., battery controller) and / or any other related device or component according to the embodiments of the present disclosure described herein can be implemented using any suitable hardware, firmware (e.g., application specific integrated circuit), software, or a combination of software, firmware and hardware. For example, the various components of the device can be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device can be implemented on a flexible printed circuit film, a tape carrier package (TCP), a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device can be processes or threads that run on one or more processors in one or more computing devices to execute computer program instructions and interact with other system components for performing the various functions described herein. The computer program instructions are stored in a memory, which can be implemented in a computing device using a standard memory device (such as a random access memory (RAM) as an example). The computer program instructions can also be stored in other non-temporary computer-readable media (such as a CD-ROM or a flash drive, etc. as an example). Furthermore, those skilled in the art will recognize that the functionality of various computing devices may be combined or integrated into a single computing device, or the functionality of a particular computing device may be distributed across one or more other computing devices without departing from the scope of the embodiments of the present disclosure.
[0191] While the present disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the disclosure is not limited to the disclosed embodiments, but on the contrary is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A positive electrode for a rechargeable lithium battery, the positive electrode for a rechargeable lithium battery comprising: current collector; A positive electrode active material layer, comprising a positive electrode active material; as well as a heat suppression layer, located between the current collector and the positive electrode active material layer, Wherein, the thickness ratio of the heat suppression layer to the positive electrode active material layer is 1:5 to 1:
20.
2. The positive electrode for a rechargeable lithium battery according to claim 1, wherein The heat suppression layer includes a compound for suppressing heat generation, and the compound for suppressing heat generation is FeF3, FeF2, CuF2, MoCl5, NiF2, FeCl3, CoF3, CoF2, MnF3, NbF3, TiF4, ZnF2, BiF3, TiO2, SeO2, CuO, CuO2, P2S5, P4S7, NiS2, CoS2, Co3O4, FeS2, MoO3, SiS2, MnO2, Fe2O3, V2O5, LiFeF3, LiFeF2, LiCuF2, LiNiF2, LiFeCl3, LiCoF3, LiCoF2, LiMnF3, LiNbF3, LiTiF4, LiBiF3, LiTiO2, Li4Ti5O 12 , LiSeO2, LiCuO, Li2CuO2, Li2P2S5, LiNiS2, LiCoS2, LiCo3O4, LiFeS2, LiMoO3, Li2SiS2, LiMnO2, LiFe2O3, LiV2O5, Li2S8 and at least one of their combinations.
3. The positive electrode for a rechargeable lithium battery according to claim 2, wherein The compound for suppressing heat generation is at least one of FeF3, TiO2, LiFeF3, LiFeF2 and a combination thereof.
4. The positive electrode for a rechargeable lithium battery according to claim 1, wherein A thickness ratio of the heat suppression layer to the positive electrode active material layer is 1:8 to 1:
15.
5. The positive electrode for a rechargeable lithium battery according to claim 1, wherein The heat suppression layer has a thickness of 1 μm to 10 μm.
6. The positive electrode for a rechargeable lithium battery according to claim 1, wherein The heat suppression layer has a thickness of 1 μm to 8 μm.
7. The positive electrode for a rechargeable lithium battery according to claim 1, wherein The thickness of the positive electrode active material layer is 30 μm to 200 μm.
8. The positive electrode for a rechargeable lithium battery according to claim 2, wherein The compound for suppressing heat generation is in a nano-size level.
9. The positive electrode for a rechargeable lithium battery according to claim 2, wherein: The compound for suppressing heat generation has an average particle size of 1 μm or less.
10. The positive electrode for a rechargeable lithium battery according to claim 2, wherein The heat suppression layer further includes a binder.
11. The positive electrode for a rechargeable lithium battery according to claim 10, wherein The binder includes polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon or a combination thereof.
12. The positive electrode for a rechargeable lithium battery according to claim 1, wherein The heat suppression layer includes a compound for suppressing heat generation and a binder, and a mixing ratio of the compound for suppressing heat generation and the binder is 200:1 to 20:1 by weight.
13. A rechargeable lithium battery, comprising: The positive electrode according to any one of claims 1 to 12; A negative electrode, including a negative active material; as well as Electrolytes.